Poluentes orgânicos persistentes em ar interior: desenvolvimento de método de extração em adsorvente para amostragem ativa - Teixeira Júnior, Ovídio José [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Persistent Organic Pollutants (POPs) are chemical substances extraordinarily toxic and persistent in the environment. Due to these properties, POPs are targets of the Stockholm Convention which aims to provide means to eliminate production and use by encouraging the reduction and, where possible, eliminating the release of these contaminants to the environment. One of the articles of this _Convention aims to assess the basal levels of such substances in the environment to monitor both the reduction of release to the environment, and to assess human exposure, using analyzes of milk and air for example. Although efforts to control POPs production and release to the environment have been made, data about their levels in Brazil are still scarce, mainly in the atmosphere or indoor environment. Considering the permanence of people inside its house, this study presents a method for POP extraction from XAD-2 sorbent employed in indoor air sampling, with identification and quantification by GC-ECD. GC-ECD linear range of the studied analytes, congeners of polychlorinated biphenyls (PCB) (28, 52, 101, 118, 138, 153 and 180), DDTs and their metabolites (DDDs, DDEs) and endosullan (isomers c - and 13 - and metabolite endosulfan sulfate) ranged between 0.5 and 16.0 ng mL-I with r2 > 0.967. The method developing consist of selecting the extraction solvent system by agitation (90 rpm, 1 hour) with n-hexan,e (2 mL) or n-hexane:acetone (1:1, v/v) (2 mL), concentration the extract with a gentle N2 stream, and evaluation of breakthrough with passage or air through the fortified XAD-2 cartridge before extraction, employing a low volume air suction pump (Pump Model 224 universal-PCXR8; 5-5000 mL min-1, SKC Inc., Eighty Four, PA, USA), Calibrator Dry-Cal DC-Lite (BIOS, Butler, NJ, USA)). Two fortification levels were employed, 15 and 30 ng. After selecting n-hexane as extraction solvent, with accuracy and precision ranging...

Os Poluentes Orgânicos Persistentes (POP) são substâncias químicas extraordinariamente tóxicas e persistentes no ambiente. Devido a essas propriedades, os POP são alvos da Convenção de Estocolmo que visa proporcionar meios para eliminar a produção e o uso, incentivando a redução e, quando possível, a eliminação da liberação desses contaminantes para o ambiente. Um dos artigos da Convenção visa a avaliação dos níveis basais dessas substâncias no ambiente para acompanhar tanto a redução da liberação das mesmas no ambiente, quanto para avaliar a exposição humana a esses compostos, empregando análises de leite materno e ar, por exemplo. Apesar dos esforços para controlar a produção e a liberação desses poluentes para o meio ambiente, Os dados sobre os níveis no Brasil ainda são escassos, principalmente na atmosfera e ambiente interno. Considerando a permanência das pessoas dentro de suas residências e ambientes de trabalho, este estudo apresenta um método para extração de alguns POP do adsorvente XAD-2, empregado na amostragem de ar interior, com identificação e quantificação por cromatografia gasosa e detector de captura de elétrons (GC-ECD). O intervalo de trabalho e a linearidade do GC-ECD para os analitos estudados, congêneres das bifenilas policloradas (PCBs) (28, 52, 101, 118, 138, 153 e 180), DDTs e os seus metabólitos (DDDs, DDEs) e endossulfam (isômeros a- e p- e o metabólito endossulfam sulfato), variou entre 0,5 e 16,0 ng mL-I com r2 0,967, respectivamente. O desenvolvimento do método contemplou a escolha de sistema de extração dos analitos da resina XAD-2, agitação (90 r.p.m, 1hora) com n-hexano (2mL) ou n-hexano: acetona (1:1) (2mL), concentração do extrato com fluxo brando de N2 e avaliação do breakthrouhg, com passagem de ar pelos cartuchos fortificados antes da extração empregando bombas de sucção de ar de baixo volume...
Keywords: Quimica analitica; Química ambiental; Amostragem